2021
DOI: 10.3389/fnut.2020.570235
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan Fasting During the COVID-19 Pandemic; Observance of Health, Nutrition and Exercise Criteria for Improving the Immune System

Abstract: Fasting is one of the religious rituals of Muslims worldwide who refrain from eating foods and liquids every year during Ramadan. This year (2020), Ramadan is very different from previous years due to the outbreak of a terrible microscopic giant called coronavirus disease 2019 (COVID-19). The pandemic COVID-19 has made Ramadan very important this year because the virus has infected millions of people around the world and killed thousands, especially people with immunodeficiency. In dealing with COVID-19, maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 93 publications
1
33
0
3
Order By: Relevance
“…The present study found that the utilization of indoor protection (32.9%) was lower than that of outdoor protection (72.1%), results similar to those of a previous study [ 29 ]. Indoor preventive behaviours could easily be overlooked for various reasons.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study found that the utilization of indoor protection (32.9%) was lower than that of outdoor protection (72.1%), results similar to those of a previous study [ 29 ]. Indoor preventive behaviours could easily be overlooked for various reasons.…”
Section: Discussionsupporting
confidence: 92%
“…Indoor preventive behaviours could easily be overlooked for various reasons. Exercise and nutritional supply were more focused on immunity improvement, but its effect was not as immediate [ 29 ]. Weak perception by the residents was manifested by a lack of identification with the information, leading to superficial and ineffective information processing [ 13 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, special attention should be paid to the adjustment of negative emotions. Studies have shown that medical workers are more likely to have psychological problems (14,15). So far, the global epidemic prevention and control is still in a critical period, and some areas have been in a state of resumption of work.…”
Section: Introductionmentioning
confidence: 99%
“…With more than 150 million confirmed cases and more than 3 million reported deaths, the pandemic has been a worldwide tragedy, with consequences impacting far beyond these numbers. In addition to the health disaster in all the countries in the world, the control measures had important consequences, not only the expected socioeconomic derivatives but also emotional ( 1 , 2 ), educational ( 3 , 4 ), or cultural ( 5 , 6 ) consequences, to cite but a few. Therefore, this emergency situation has required constant monitoring at multiple levels—from the city neighborhood tracking of local outbreaks to a global continental perspective for socioeconomical decisions coordinated at the interstate level.…”
Section: Introductionmentioning
confidence: 99%